Measuring patient activation: The utility of the Patient Activation Measure within a UK context—Results from four exemplar studies and potential future applications. Issue 10 (October 2016) - Roberts, N.J.; Kidd, L.; Dougall, N.; Patel, I.S.; McNarry, S.; Nixon, C.
Highlights: The patient activation measure is a useful tool to measure readiness to engage. PAM scores can help tailor support for those with long term conditions. The PAM tool should not be used without clinical and sociodemographic information. Further work is needed to monitor PAM through the patient journey. Abstract: Objective: Patient activation can be measured using the Patient Activation Measure (PAM) developed by Hibbard et al., however, little is known about the uses of the PAM in research and in practice. This study aims to explore its differing utility in four UK exemplar sites. Methods: Data from four exemplars in a range of health settings with people living with long-term conditions (i.e. stroke or COPD) were evaluated. PAM scores were described and explored in relation to clinical and sociodemographic variables and outcome measures. Results: PAM scores illustrated that most with COPD or stroke reported PAM levels of 3 or 4, indicating that they are engaging, but may need help to sustain their scores. The exemplars illustrate the utility of, and potential issues involved in, using PAM as a process/outcome measure to predict activation and the effectiveness of interventions, and as a tool to inform tailoring of targeted interventions. Conclusions: The PAM tool has been shown to be useful as an outcome measure, a screening tool to tailor education, or a quality indicator for delivery of care. Practice implications: However good demographic and patient historyare needed to substantiate PAM scores. Further work is needed to monitor PAM prospectively.